\(x=cy+bz-----(i)\)
\(y=az+cx-----(ii)\)
\(z=bx+ay-----(iii)\)
\((i) \) নং সমীকরন থেকে পাই,
\(x=cy+bz\)
বা, \(x=cy+b(bx+ay)\)
[\((iii) \) নং সমীকরনের \(z\) এর মান বসিয়ে]
বা, \(x=cy+b^2x+aby\)
বা, \(x^2=cxy+b^2x^2+abxy-----(iv)\)
[উভয় পক্ষকে \(x\) দিয়ে গুন করে পাই]
\((ii) \) নং সমীকরন থেকে পাই,
\(y=az+cx\)
বা, \(y=a(bx+ay)+cx\)
[\((iii) \) নং সমীকরনের \(z\) এর মান বসিয়ে]
বা, \(y=abx+a^y+cx\)
বা, \(y^2=abxy+a^2y^2+cxy-----(v)\)
[উভয় পক্ষকে \(y\) দিয়ে গুন করে পাই]
\((iv)\) নং সমীকরন থেকে \((v)\) নং সমীকরন বিয়োগ করে পাই,
\( x^2-y^2=b^2x^2-a^2y^2\)
বা, \( x^2-b^2x^2=y^2-a^2y^2\)
বা, \(x^2(1-b^2)=y^2(1-a^2)\)
বা, \(\cfrac{x^2}{1-a^2}=\cfrac{y^2}{1-b^2}\) (প্রমাণিত)